Mechanical and Thermal Properties of Polylactic Acid and Plasticized Polylactic Acid with Thermoplastic Sago Starch Blends - E. Mahgoub, Eyman (2004)
The aim of this study was to produce plasticized blends of Polylactic acid,to evaluate the effect of two plasticizers Triethyl citrate (TC) and thermoplastic sago starch (TSS) on the mechanical and thermal properties of PLA and to evaluate the combined effect of plasticizers (TC and TSS) on the mechanical and thermal properties of PLA.The biodegradable polymer blends were prepared with various concentrations of triethyl citrate and thermoplastic sago starch in order to obtain a plastic material with a range of different mechanical properties that are suitable for packaging applications.The blends were melted by using twin-screw extruder.The samples obtained were examined for the effect of TC and TSS addition on thermal transitions and mechanical properties.The blends were characterized by Differential scanning calorimetry (DSC) for thermal transitions and by Instron testing machine for tensile strength, young modulus, elongation, and toughness.The addition of a plasticizer TC to a polymer PLA decreased the tensile strength and young modulus while increased the elongation at break and toughness. The addition of TC also shifted the glass transition temperature (Tg) down to lower temperatures and no crystallization of PLA was observed.The behavior of the PLA/TSS blends did not follow the same trend in all the compositions.Tensile strength and modulus decreased for PLA/TSS blends with 10% and 30% of TSS when compared to pure PLA, the elongation at break decreased insignificantly and no improvement in toughness was observed. On the other hand,PLA/TSS blend with 20% TSS had the highest tensile strength and elongation,but lowest modulus compared to pure PLA and other blends. A clear single Tg was observed for each of the PLA/TSS blends indicating high level of miscibility in each blend and the value of Tg decreased with the addition of TSS, with unstable trend.The PPLA/TSS blends varied in their mechanical properties and no obvious trend was observed when investigating the effect of TC or addition of TSS on the mechanical properties.This might be attributed to: first the nature of specimens, in which non homogenousity was observed obviously and second the anti plasticizing effect that appears in some of the PPLA/TSS blends containing 10% and 30% TSS due to additionof insufficient amounts of Plasticizer